High frequency wide beam PVDF ultrasonic projector for underwater communications - Martins, M. S. (2019)
This work describes the development and characterization of a wide beam and wideband ultrasonic transducer, designed as an emitter for underwater communications up to 1.5 MHz. The active element being used is composed of two layers of 110 mu m PVDF (Polyvinylidene fluoride) film, with NiCu electrodes. The transducer has a semicircular shape with a diameter of 15 cm. Pool trials show a transmitting voltage response of approximately 150 dB re mu Pa/V @ 1m from 750kHz to 1MHz and higher than 130 dB re mu Pa/V @ 1m between 250kHz and 1.5MHz. At 1 MHz, when excited with 12V, the transducer has a power consumption of 37.5 mW.